Study on application of green-synthesized ZnO and Si nanoparticles in enhancing aquaculture sediment quality - Yaoqiang Zhu; Weidong Li; Waqas Ahmed; Mohsin Mahmood; Hayssam M. Ali; Muhammad Rizwan; Jochen Bundschuh; Muhammad Akmal; Sajid Mehmood (Chemical and Biological Technologies in Agriculture)
Abstract Background Fishpond sediments (FPS) are rich in organic carbon and nutrients, making them valuable as fertilizers and soil conditioners. Stabilizing heavy metals like chromium (Cr), copper (Cu), and zinc (Zn) is essential to reduce their bioavailability and risks. This study evaluates zinc oxide (ZnO) and silicon (Si) nanoparticles synthesized from Azolla pinnata and Equisetum arvense for heavy metal immobilization and nutrient enhancement in FPS from San Jiang (SJ) and Tan Niu (TN), China. Methods Nanoparticles were synthesized using Azolla pinnata and Equisetum arvense. Fishpond sediments from San Jiang (SJ) and Tan Niu (TN) were treated with ZnO and Si nanoparticles. Heavy metals and nutrients were analyzed via ICP-OES and soil analysis, while sequential extraction assessed metal distribution in geochemical fractions. Results The application of these nanoparticles, especially the green-synthesized zinc oxide nanoparticles (GSZnONPs), was found to significantly reduce the concentrations of chromium (Cr), copper (Cu), and zinc (Zn) in both the overlying and pore water of the FPS. This reduction not only minimizes the leachability of these heavy metals, but also substantially decreases their bioavailability. The study recorded a notable shift in the acid-soluble metal fraction, resulting in an average reduction of Cr concentrations by 31–28%, Cu by 18–21%, and Zn by 32–23% in the sediments from San Jiang (SJ) and Tan Niu (TN). Moreover, the application of these nanoparticles also improved the nutrient profile of the sediments, potentially enhancing their utility as fertilizers. Conclusion Zinc oxide and silicon nanoparticles synthesized from Azolla pinnata and Equisetum arvense are effective in immobilizing heavy metals in fishpond sediments, significantly reducing their bioavailability and potential environmental risks. The use of these green-synthesized nanoparticles not only mitigates heavy metal contamination, but also enhances the nutrient content of the sediments, making them more suitable for use as soil conditioners and fertilizers. This dual benefit highlights the potential of these nanoparticles as a sustainable solution for managing contaminated fishpond sediments while contributing to agricultural productivity. Graphical Abstract